Evaluation of Regional Asset Management at the Financial and Asset Management Agency of Sikka Regency - Elsari, Maria Nining; Lamawitak, Paulus Libu; Patty, Thadeus Fransesco Quelmo; Lewar, Maria Viviana Nurak (International Publisher (YAPENBI), 2026)
This research aims to evaluate the implementation of regional asset administration (Barang Milik Daerah/BMD) at the Regional Financial and Asset Management Agency (BPKAD) of Sikka Regency. The study assesses the conformity of asset administration practices, including bookkeeping, inventory, and reporting, with applicable regulations, particularly the Regulation of the Minister of Home Affairs Number 19 of 2016 and Number 47 of 2021. This Research employs a qualitative descriptive method with a case study approach. Data were collected through direct observation, interviews with asset management officers, and analysis of documentation during the internship program. The results indicate that the implementation of BMD administration at BPKAD Sikka Regency generally follows established regulations, but its execution has not been optimal. Several obstacles were identified, including limited human resources, low mastery of information technology, and inadequate supporting facilities and infrastructure. These constraints have caused delays and inaccuracies in asset recording, inventory, and reporting processes. Therefore, efforts are needed to improve human resource capacity through continuous technical training, strengthen asset management information systems, and provide adequate facilities.